A new apparatus to establish the spontaneous combustion propensity of coals and coal-shales - Onifade, M.; Genc, B.; Carpede, A. (International journal of mining science and technology, 2018)
Coal and coal-shale both tend to undergo spontaneous combustion under favourable atmospheric conditions. The Wits-Ehac index has been developed in South Africa since the late 1980’s to test the spontaneous combustion liability of coal. However, in some cases, the Wits-Ehac index fails to produce tangible results when testing coal-shales. To overcome this problem, a new apparatus has been developed to test carbonaceous materials such as coal and coal-shale under chemical reactions with oxygen and an index has been obtained. This index is called the Wits-CT index. The equipment emulates the influence of oxygen adsorption on carbonaceous material for a period of 24 h without a heating system. The Wits-CT index uses the total carbon content of the sample and the temperature variations obtained from the samples during reaction with oxygen to predict the spontaneous combustion liability. Eighteen samples have been analyzed using both indices and the results are in-line. It was found that coals and coal-shales with higher values of the Wits-CT index are more liable to spontaneous combustion. Further research on different coal-shales is underway in order to establish an extensive database for coal and coal-shales, together with known incidences of self-heating.